Número 14 (La Lupa. Colección fueguina de divulgación científica, 2019)
Comité EditorialAnna Franch BachTomás Ignacio MarinaAdriana LasaValeria BartoliCatherine RoulierJulieta KaminskyUlises BalzaMaría GranittoNélida PalVictoria Julieta GarcíaDiseño y DiagramaciónIrina Castro PeñaUshuaia, Tierra del Fuego, ArgentinaE-mail: iricastrop@gmail.comMantenimiento informático y técnicoFernando Gini (CADIC)ImpresiónM&A Diseño y Comunicación S.R.L.Buenos Aires, ArgentinaE-mail: info@myaweb.com.ar